Potentials and limitations of RFID applications in packaging industry: a case study. (1st October 2010) - Seidel, Thomas; Donner, Reik
The application of radio frequency identification (RFID) technology has been intensively discussed as an innovative technique for improving performance and, hence, assessing economic potentials in manufacturing systems. However, a systematic application in different industries has not yet been achieved. In this paper, we present a case study revealing the potentials and limits of the use of RFID in packaging plants. It is demonstrated that in such factories, there are two important fields of application of RFID and related technologies: inventory control of finished and temporally stored products and transfer control of individual goods within the transport and buffer system linking the different machines. We present a general framework of how RFID technology can be implemented for these two purposes, supporting the existing infrastructure. Our findings may be generalised to a variety of other manufacturing industries.